Efficacy and suitability of whole wheat flour on the growth and survival of Rohu (Labeo rohita) - Sarker, Shovon; Rohani, Md Fazle; Rahman, Md Shafiqur; Hossain, Md Sazzad (Research in Agriculture Livestock and Fisheries, 2019)
The efficacy and suitability of dietary whole wheat flour supplementation was evaluated on the growth performance and survival of rohu (Labeo rohita). The study was conducted in 12 experimental aquaria at the Wet Laboratory, Department of Aquaculture, Bangladesh Agricultural University, Mymensingh. A total of 180 fingerlings of mean initial weight of 1.744±00 g were stocked at the same stocking density (268 fingerlings/m3). Four different treatments (T1, T2, T3 and T4) each with three replications were performed having different level of whole wheat flour such as 0% whole wheat flour (T1), 5% whole wheat flour (T2), 10% whole wheat flour (T3) and 15% whole wheat flour (T4). Feeds were supplied at 5% body weight twice daily in the morning at 9.00 am and in the afternoon at 5.00 pm throughout the study period. The rations were adjusted every week when new weights of the fish for various experimental aquariums were determined. At the end of the 63 days study period, the growth performance parameters such as mean final weight (g), weight gain (g), percent weight gain (%), specific growth rate (%/day) and the best feed utilization in terms of food conversion ratio were found highest at treatment 4 where fishes were fed with inclusion of 15% whole wheat flour and lowest was found at treatment 1 (fed with inclusion of 0% whole wheat flour). Water quality parameters were within the acceptable range and survival rate was found 100% in all treatment. Therefore, it can be concluded that treatment 4 (highest growth performance and survival rate of L. rohita with supplementation of 15% whole wheat flour containing diet) can be chosen by fish farmers for commercial culture of this species. Res. Agric., Livest. Fish.6(2): 345-352, August 2019